Including colon in intestinal transplantation: a focus on post‐transplant renal function – a retrospective study. (10th October 2019) - Ewald, Cale; Swanson, Benjamin J.; Vargas, Luciano; Grant, Wendy J; Mercer, David F.; Langnas, Alan N.; Merani, Shaheed
Summary: Intestinal transplant recipients experience a high rate of renal complications secondary to dehydration due to increased ostomy output. It is hypothesized that inclusion of donor colon in the intestinal allograft may improve renal function in patients without functional native colon by improving fluid absorption. A single‐center retrospective study of intestinal transplant recipients compared outcomes of patients receiving en bloc colon as part an intestinal allograft (ICTx), and those not receiving colon (CCNTx), as well as a control group of intestinal transplant recipients with functional native colon (ITx). Forty‐seven patients (ICTx n  = 17, CCNTx n  = 15, ITx n  = 15) were studied. One‐year post‐transplant renal function, as measured by change in glomerular filtration rate (GFR) and blood urea nitrogen (BUN) from baseline, was superior in ICTx (mean delta‐GFR of −1.31 and delta‐BUN of −1.46) compared to CCNTx (−6.54 and 17.54, P  = 0.05 and P  = 0.17, respectively) and similar to the ITx controls (0.55 and 2.09). Recipients of donor colon experienced a higher rate of ileostomy reversal when compared to CCNTx (62.5% vs. 20%, P  = 0.0008), which was similar to the ITx controls (60%). These findings support the inclusion of en bloc donor colon in the intestinal allograft for recipients without functional native colon.